Animal Meaning: Review of Linda Kalof and Georgina M. Montgomery, eds. Making Animal Meaning - Cronin, J. Keri (Humanimalia, 2013)
Linda Kalof and Georgina M. Montgomery, eds. Making Animal Meaning. East Lansing: Michigan State UP, 2011. 212 pp. $44.95 hb, 32.95 pb.